QALBU, FUNCTIONAL AND GENERIC: REQUIREMENTS FOR THE APEX STUDENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, August 2015 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman said, the students involved in the Accelerated Programme for Excellence (APEX) should be wellequipped and outstanding in fulfilling the three stages of the “Pimpin Siswa Lestari” (orientation programme) canvas, namely through Qalbu, Functional and Generic as well as in acquiring various skills, and not just by merely accumulating MyCSD points.